Implications of the Mind’s Active Participation in the Formation of Perception - Michael, Maikel Adel Samy (AUC Knowledge Fountain, 2025)
The mind-body problem, particularly the issue of qualia, remains a fundamental challenge in understanding the nature of the mind and its relation to the body. In this thesis I argue that the problem is epistemic, stemming from how we perceive and know ourselves as physical and mental beings. This argument will be explored through the respective of idealisms proposed by George Berkeley and Immanuel Kant. Berkeley's idealism suggests that reality is rooted in perception, offering a major steppingstone by demonstrating the major role perception plays in understanding and acquiring knowledge. Kant contributes by asserting that the "thing-in-itself" is beyond our empirical grasp, and our perceptions do not fully represent the mind's true nature. Our understanding is limited to phenomena, not noumena, leading to the persistence of the explanatory gap. In this thesis I propose that this limitation might be evolutionarily advantageous, as the mind evolved as a survival tool rather than a means for uncovering ultimate truths. This perspective suggests that our restricted perceptive access has evolved to prioritize survival through recognizing faces, dangers, and the like, rather than exploring the deepest truths of our nature and reality. Thus, the mind-body problem reflects the inherent limitations of human perception and knowledge in the pursuit of understanding our fundamental nature.